Intermediate and Long-Term Outcomes of the Universal 2 Total Wrist Replacement - Truss, Adam; Morris, Geraint; Sawalha, Seif; Waseem, Mohammad (Journal of Wrist Surgery, 2023)
Introduction Arthritis of the wrist can lead to severe functionally debilitating pain which, after failed conservative measures, may require treatment with total wrist replacement (TWR). Various prosthetic designs, such as the Universal 2 implant, have been developed in attempts to combat the multitude of complications faced with replacing a complex and highly mobile joint. Having previously published short-term outcome results for the Universal 2 prosthesis, we now present the long-term survival data.Materials and Methods 19 patients underwent 21 TWR using the Universal 2 prosthesis between September 2004 and March 2008. Outcome data were collected in the form of Patient-Rated Wrist Evaluation (PRWE) and Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaires at short- (mean 4.8 years), intermediate- (mean 11.1 years), and long-term (mean 15.6 years) intervals. Nonparametric and Kaplan–Meier survival analysis was performed.Results At long-term follow-up, 7 out of the original 21 TWRs had required a revision or fusion procedure, or 7 out of 11 when excluding those lost to follow-up or who had died. At the intermediate follow-up, only one patient had required a revision procedure. Kaplan–Meier survival analysis demonstrated a median survival of 12.9 years and a 10-year survival probability of 68.1%. There was a statistically significant improvement from preoperative PRWE at short-term (p = 0.001) and intermediate (p = 0.01) follow-ups. This was not seen at the long-term follow-up (p = 0.068). After an initial improvement in DASH score at short-term follow-up (p = 0.003), the intermediate and long-term DASH scores were not significantly different from preoperative.Conclusion The Universal 2 poses a reasonable TWR implant choice for patients with debilitating arthritis. However, despite excellent short-term follow-up outcomes, longer term follow-up shows the design does continue to be plagued by implant failure and instability.
Keywords: Universal 2; total wrist replacement; wrist arthroplasty